2018
DOI: 10.1016/j.jvs.2018.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Outcomes of Ipsilateral Antegrade Angioplasty for Femoropopliteal Disease

Abstract: stent deployment) compared to peaking several days postoperatively after CEA. This large retrospective cohort study found that the risk of ICH was significantly higher after CAS (0.85%) than CEA (0.42%). However, this difference may not be clinically significant. This discrepancy in ICH was not due to differences in preprocedure antiplatelet or anticoagulant. Many factors were not assessed, such as the degree of contralateral disease, plaque characteristics, and, most importantly, postprocedure dual antiplatel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Cragg et al 21 reported in a prospective study of 556 patients undergoing femoropopliteal angioplasty that compared with femoral RA, AA did not have a significantly higher rate of access site complications (AA, 3.7% vs RA, 1.1%; P ¼ .186), which were defined as retroperitoneal hematoma, pseudoaneurysm, hematoma requiring transfusion, arteriovenous fistula formation, acute thrombosis, and need for surgical repair. Although not statistically significant, Cragg et al 21 complications, including hematoma, between femoral RA and AA, although this study did not report on the use of CDs.…”
Section: Discussionmentioning
confidence: 94%
“…Cragg et al 21 reported in a prospective study of 556 patients undergoing femoropopliteal angioplasty that compared with femoral RA, AA did not have a significantly higher rate of access site complications (AA, 3.7% vs RA, 1.1%; P ¼ .186), which were defined as retroperitoneal hematoma, pseudoaneurysm, hematoma requiring transfusion, arteriovenous fistula formation, acute thrombosis, and need for surgical repair. Although not statistically significant, Cragg et al 21 complications, including hematoma, between femoral RA and AA, although this study did not report on the use of CDs.…”
Section: Discussionmentioning
confidence: 94%
“…AA scores over RA by avoiding difficult inflow anatomy and reducing the contrast agent and radiation dose (1,3). However, AA is more likely to be associated with procedure-induced complications, such as retroperitoneal hematoma in cases with a high puncture site in the EIA (1,2). Therefore, ultrasound-guided CFA puncture is recommended.…”
Section: Discussionmentioning
confidence: 99%
“…Surgery is indicated even in hemodynamically stable patients in the event of endovascular treatment failure or in patients in whom an appropriate graft is unavailable. However, identification of the bleeding site is often challenging, and surgery is usually associated with significant morbidity and mortality (1,6). Therefore, aortic occlusion is an acceptable alternative for hemostasis to achieve temporary hemodynamic stabilization and restore blood pressure in patients with hemorrhagic shock secondary to RPH.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations